The Tobacco Epidemic in Southeast Europe : Consequences and Policy Responses - Bozicevic, Ivana; Gilmore, Anna; Oreskovic, Stipe (World Bank, Washington, DC, 2013)
Smoking is the single largest cause of premature mortality in the developed world. Obtaining accurate estimates of smoking's impacts in south east Europe (SEE) is hindered by the lack of accurate data.. None of the countries of the region yet conduct regular national surveys of adult smoking prevalence and some have no recent nationally representative data available. The very high rates among medical personnel are cause for concern. Youth smoking surveys are now conducted in most countries as part of international projects and show rates broadly similar to the EU. The collapse of communism and the end of the conflicts in the 1990s has led to major changes in the region's tobacco industry. The previously state-owned tobacco monopolies have either undergone or are undergoing privatization and the transnational tobacco companies have been increasingly active both in importing their cigarettes to, and investing in, the region. These changes can be expected to increase competition in the tobacco industry which will in turn drive down prices and increase advertising, thereby stimulating consumption. The available statistics, combined with the changes to the region's tobacco industry, suggest that the health impacts of tobacco in SEE will continue to worsen over coming years.